DAMPAK SISTEM ZONASI DALAM PERMENDIKBUD NO. 20 TAHUN 2019 DI KABUPATEN PAMEKASAN - Mohammad Nurul Huda; Ach. Khoiri (Nurul Jadid University, 2020)
Regulation of the Minister of Education and Culture Number 20 of 2019 concerning Amendments to the Regulation of the Minister of Education and Culture Number 51 of 2018 concerning the Admission of New Students in Kindergartens, Elementary Schools, Junior High Schools, Senior High Schools, and Vocational High Schools is a guideline for public schools from kindergarten to high school level to implement the Zoning system for the admission process of new students.The purpose of this research is to find out and analyze the effectiveness of the enactment of the minister of education and culture regulation number 20 of 2019 for schools, students, and parents / guardians in Pamekasan. This research uses empirical methods or non-doctrinal research. This type of research was chosen because the subject of the research plan seeks to trace and study the impact of the enactment of the minister of education and culture regulation number 20 of 2019 for schools, students, and parents in Pamekasan.Of the 220 respondents, divided from teachers, parents / guardians and students, the results of the respondents' level of understanding of the Zoning system PPDB really understood. Schools disobedience to PPDB Zoning system are private schools and schools that are under the auspices of the Ministry of Religion. In addition, the ineffectiveness of the PPDB Zoning system in Pamekasan Regency is the result of the many educational institutions that are under the auspices of Islamic boarding schools.